Perbedaan Kekerasan Permukaan Resin Komposit Nanohybrid Setelah Direndam Minuman Soda Bergula dan Beraspartam - Rahayu Sukma Dewi; Laksmiari Setyowati; Agus Subiwahjudi (Universitas Airlangga, 2018)
Background: Nanohybrid composite has filler with variation of size and contain nano-sized particles. The decreasing of surface hardness can be occured because consumption of acid pH beverages, carbondioxide (CO2) from soft drinks and water. Sugary soft drink (coca-cola) has lower pH than aspartame soft drink (coca-cola zero). Besides the difference of pH, aspartame soft drink (coca-cola zero) contains fenilalanin amino acid the product of hydrolisis reaction of aspartame so the acid environment become neutral. Purpose: To view the differences of nanohybrid resin composite after being soaked in sugary soft drink and aspartame soft drink. Methods: There are significant differences between samples being soaked in aquades and aspartame soft drink (coca-cola zero) and sugary soft drink (coca-cola). There are significant differences between aspartame soft drink (coca-cola zero) and sugary soft drink (coca-cola). Conclusion: Surface hardness of nanohybrid resin composite is lower after being soaked in sugary soft drink (coca-cola) than after being soaked in aspartame soft drink (coca-cola zero).